Clusterization Algorithms in Multifragmentation - Bansal, Ekta (My University, 2010)
In the present thesis, we analyze the formation of fragments in two different reactions at different incident energies129Xe54+197Au79 at E=50MeV/nucleon and 36Ar18+197Au79 at E=50, 80,110MeV/nucleon at different impact parameters using hard and soft equations of state. For the present analysis, Isospin Dependent Quantum Molecular Dynamics Model (IQMD) is used as an event generator. To address the stability of fragments, we employ two different clusterization algorithms methods i.e. Minimum Spanning Tree method (MST), Minimum spanning tree with momentum cut (MSTP) and Minimum Spanning Tree with Binding Energy Check (MSTB). Our analysis shows that the fragment created are not stable even at 100 fm/c and an additional binding energy checks helps to discard the unbound fragments and as result the modified MST (with the binding energy check) identifies the fragments early. The comparison is performed for the free nucleons as a function of impact parameter using hard equation of state with experimental data in two different reactions at different incident energies. The MSTB method can be applied whenever one wants to identify the fragments which are of given number of constituents form bound objects.
M.Sc. (Physics)
Keywords: clusterization; heavy ion reactions